Term alive intra abdominal ectopic pregnancy - Abeda, K; Akter, L (Bangladesh Journal of Medical Science, 2012)
A case of term alive intra abdominal ectopic pregnancy. This case is a rarity that a few Gynaecologists encounter during their professional carrier. Initially it was diagnosed as a case of hyperamesis graviderum and was treated conservatively. Confirm diagnosis was done during laparotomy, a female baby was delivered and the patient recovered uneventfully. DOI: http://dx.doi.org/10.3329/bjms.v11i1.9828 BJMS 2012; 11(1): 66-68